Effects of Solution Composition and Polymer Additive on the Crystallization of Struvite. Issue 7 (31st May 2017) - Liu, Yi; Qu, Haiyan
Abstract: Reject water from a wastewater treatment plant contains a large amount of phosphorus that can be recovered and used as phosphate fertilizer. However, the quality of the final products is affected by the variation of wastewater composition. This work focuses on the effects of the nitrogen/phosphorus (N/P) molar ratio, which is a mutable variable in the reject water, and a polymer additive on the crystallization of struvite from an artificial reject water system. The obtained results suggest that crystallization at a low pH (7.5) resulted in a narrow size distribution, over 93 % P could be recovered. The presence of the polymer Aquaflok 414C led to a slightly narrower crystal size distribution at a lower supersaturation index. Abstract : Phosphorus recovered from reject water from a wastewater treatment plant can be used as a phosphate fertilizer. The composition of the wastewater affects the quality of the product, so the effects of solution composition and polymer additive on the crystallization of struvite have been studied. Controlling the crystallization process guarantees the consistent production of struvite with desired properties.